Mothering, Education and Culture Russian, Palestinian and Jewish Middle-Class Mothers in Israeli Society - Golden, Deborah (Palgrave Macmillan UK, 2018)
This book is an ethnographically-informed interview study of the ways in which middle-class mothers from three Israeli social-cultural groups - immigrants from the former Soviet Union, Palestinian Israelis and Jewish native-born Israelis - share and differ in their understandings of a 'proper' education for their children and of their role in ensuring this. The book highlights the importance of education in contemporary society, and argues that mothers' modes of engagement in their children's education are formed at the junction of class, culture and social positioning. It examines how cultural models such as intensive mothering, parental anxiety, individualism, and 'concerted cultivation' play out in the lives of these mothers and their children, shaping different ways of participating in the middle class. The book will be of interest to anthropologists and sociologists studying mothering, education, parenting, gender, class and culture, to readers curious about daily life in Israel, and to professionals working with families in a multicultural context.